Der Glöckner von Notre Dame - August, Joseph H. 1890-1947; Levien, Sonya 1888-1960; Laughton, Charles 1899-1962; O'Hara, Maureen 1920-2015; Mitchell, Thomas 1892-1962; Hardwicke, Cedric 1893-1964 (Kinowelt Home Entertainment, 2004)
Een herverfilming van Lon Chaneys zwijgende rolprent.